A revision of Ceratocarcinus White, 1847, and Harrovia Adams & White, 1849 (Crustacea: Decapoda: Brachyura: Eumedonidae), two genera of crabs symbiotic with crinoids - Chia, D.G.B. (2014)
Raffles Bulletin of Zoology